Production decisions and food security outcomes of smallholder’s livestock market participation: empirical evidence from Zimbabwe - Melesse, Mequanint B.; Tirra, Amos Nyangira; Homann-kee-Tui, Sabine; Van Rooyen, Andre F.; Hauser, Michael (Frontiers Media, 2023)
Smallholder market participation is an important pathway to improving the productivity and livelihoods of farm households. Despite several studies documenting the effect of market participation on crop production, relatively little is known about the effect of smallholder participation in livestock markets. We investigate effects of smallholder market participation on livestock production and household food security in Zimbabwe. Using survey data collected from 625 households and an instrumental variables strategy to address endogeneity concerns, we find that households participating in livestock markets are more likely to engage in market-oriented livestock production, use improved livestock inputs, and have better food security outcomes. While market participants are more likely to consider market conditions in their decisions, most farmers are needs-driven and cannot afford to adopt commercial-oriented behavior. Overall, smallholder livestock production systems respond to market incentives and can support food security strategies, particularly in drylands where crop production is risky.